2019
DOI: 10.1016/j.molcel.2019.10.034
|View full text |Cite
|
Sign up to set email alerts
|

The Integrator Complex Attenuates Promoter-Proximal Transcription at Protein-Coding Genes

Abstract: The transition of RNA polymerase II (Pol II) from initiation to productive elongation is a central, regulated step in metazoan gene expression. At many genes, Pol II pauses stably in early elongation, remaining engaged with the 25-to 60-nt-long nascent RNA for many minutes while awaiting signals for release into the gene body. However, 15%-20% of genes display highly unstable promoter Pol II, suggesting that paused polymerase might dissociate from template DNA at these promoters and release a short, non-produc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
200
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(242 citation statements)
references
References 87 publications
38
200
4
Order By: Relevance
“…This finding is consistent with previous studies showing that depletion of multiple Integrator subunits can also lead to disrupted ciliogenesis 41 , and that mutations within INTS1 or INTS8 also create ciliopathy-related symptoms 42,65 . Herein, we discovered that depletion of INTS13 causes a ~2-to 10-fold upregulation in a broad collection of ciliary genes in RPE cells, which is consistent with recent work demonstrating that depletion of Integrator subunits in Drosophila cells primarily causes an increase in transcription in a subset of genes 37,38 . We posit that an increase in transcription of a broad collection of ciliary genes is sufficient to disrupt ciliogenesis by potentially overproducing specific components.…”
Section: Xenopussupporting
confidence: 90%
See 2 more Smart Citations
“…This finding is consistent with previous studies showing that depletion of multiple Integrator subunits can also lead to disrupted ciliogenesis 41 , and that mutations within INTS1 or INTS8 also create ciliopathy-related symptoms 42,65 . Herein, we discovered that depletion of INTS13 causes a ~2-to 10-fold upregulation in a broad collection of ciliary genes in RPE cells, which is consistent with recent work demonstrating that depletion of Integrator subunits in Drosophila cells primarily causes an increase in transcription in a subset of genes 37,38 . We posit that an increase in transcription of a broad collection of ciliary genes is sufficient to disrupt ciliogenesis by potentially overproducing specific components.…”
Section: Xenopussupporting
confidence: 90%
“…Denatured protein samples were then resolved on a 10% polyacrylamide gel and transferred to a PVDF membrane (Thermo Scientific, 88518). Blots were probed as previously described 37 . Samples from nuclear extract immunoprecipitation are described in the anti-FLAG affinity purification.…”
Section: Xenopusmentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of Integrator subunits has been shown to alter the transcriptional levels of certain genes (Gardini et al 2014;Elrod et al 2019;Tatomer et al 2019). Consistently, we found that depletion of functional Int11 in HEK-293T cells differentially affects more than a thousand genes ( Figure S6F).…”
Section: Depletion Of Integrator Endonuclease Subunit Leads To Dog Prsupporting
confidence: 82%
“…As there is known RNAPII accumulation at PASs at the ends of genes, it is possible that the accumulation of RNAPII at the pausing sites is a result of the same process, but coupled to promoter-proximal polyadenylation. Indeed, short transcripts at genes with unstable promoter-promoter proximal RNAPII pausing are reported in Drosophila 29 that rely on transcriptional termination by the Integrator complex 30,31 , that also functions in 3′-end processing of relatively short snRNA 32 . The prevalence of promoterproximal transcriptional termination in additional organisms and potential roles of this phenomenon in gene expression remain an active research area.…”
mentioning
confidence: 99%